Rules and Practices of Forensic Experts in the Field of Civil or Criminal Law - Krasniqi, Sedat (European Journal of Multidisciplinary Studies, 2019)
The process of conducting an examination (by the expert) ends - de facto, with the submission of a written report (the act of expertise) to the court, while - de jure, it is considered to have been completed only when the question and answer session it is held before the court. Although in actual practice it is found that there are generally no strict requirements regarding the structure of the expert acts, the statement of facts, supporting evidence, their analysis and justification of the expert’s approach to the conclusions reached are indispensable, both for the court and the parties, to appreciate the value of the expert’s opinion and why not, to professionally list the expert in relation to other specialists in the field. Paragraph 1 of Article 230 of the Code of Civil Procedure clearly states that "The opinion of the expert must be reasoned".